2017
DOI: 10.1021/acs.analchem.7b00164
|View full text |Cite
|
Sign up to set email alerts
|

Gas Cluster Ion Beam Time-of-Flight Secondary Ion Mass Spectrometry High-Resolution Imaging of Cardiolipin Speciation in the Brain: Identification of Molecular Losses after Traumatic Injury

Abstract: Gas cluster ion beam-secondary ion mass spectrometry (GCIB-SIMS) has shown the full potential of mapping intact lipids in biological systems with better than 10 μm lateral resolution. This study investigated further the capability of GCIB-SIMS in imaging high-mass signals from intact cardiolipin (CL) and gangliosides in normal brain and the effect of a controlled cortical impact model (CCI) of traumatic brain injury (TBI) on their distribution. A combination of enzymatic and chemical treatments was employed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 48 publications
1
57
0
Order By: Relevance
“…These regions are known to be involved in memory formation, seizure, and neurodegeneration. 54 This indicated that there might be a relationship between CLs and cognition.…”
Section: Pharmaceuticalsmentioning
confidence: 97%
See 1 more Smart Citation
“…These regions are known to be involved in memory formation, seizure, and neurodegeneration. 54 This indicated that there might be a relationship between CLs and cognition.…”
Section: Pharmaceuticalsmentioning
confidence: 97%
“…To investigate the effect of traumatic brain injury on the molecular structure of the brain, Tian et al 54 developed a dynamic reactive ionization method for ToF-SIMS with a 20 keV (CO 2 ) 3500 + GCIB via treatment of the brain tissue with 1ethyl-3-[(dimethylamino) propyl] carbodiimide hydrochloride and phospholipase C (EDC/PLC). The EDC/PLC sample treatment was shown to suppress the signal of highly abundant phospholipids, especially PCs, and enhance the signal of high mass cardiolipin (CL) (m/z 1300-1530) and gangliosides (GM1, GD1, and GT1) (m/z > 1500) in the brain.…”
Section: Pharmaceuticalsmentioning
confidence: 99%
“…Some examples of this application include the localisation of dietary substrates in the brain or lipid changes in the brain after traumatic injury. 218,219 Studies of cells have also been done with IMS. As with tissue, lipid changes have been observed in both neuronal cell cultures and PC12 cells.…”
Section: Applications For Studying Cellular Signalling and Exocytosismentioning
confidence: 99%
“…216 Lipids also have the potential to show tumor boundaries, specifically in breast cancer. 217 Because of their diverse structure, several common ionization sources, including MALDI, 1,20,42,97 DESI, 22,217,218 SIMS, 219221 and IR-MALDESI, 18,19 have found success in lipid imaging. Notably, newly developed laser spray ionization (LSI), with its simple sample preparation, is becoming more commonly used for lipids as well.…”
Section: Biological Applicationsmentioning
confidence: 99%